An Investigation of Code Cycles and Poltergeist Anti-pattern - Al-Rubaye, Samer Raad Azzawi; Selcuk, Yunus Emre (IEEE, 2017)
The aim of this paper is to propose a method for detecting the Poltergeist anti-pattern. Anti-patterns are poor designs that lower software quality, especially by increasing complexity and decreasing maintainability. As maintenance of software projects costs as much as their development, it is necessary to detect poorly designed code and refactor it.
Keywords: anti-patterns; poltergeist; cycle detection; Computer Science; Engineering